2015
DOI: 10.5582/bst.2015.01057
|View full text |Cite
|
Sign up to set email alerts
|

C35 is overexpressed in colorectal cancer and is associated tumor invasion and metastasis

Abstract: SummaryThe aim of this study was to investigate the expression of C35, an oncogene previously found in breast and prostate cancers, and its clinicopathological significance in colorectal cancer (CRC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“… 4 , 9 Recently, MIEN1 was reported to be overexpressed in colorectal cancer tissue, and MIEN1 expression level was closely associated with tumor serosal invasion, lymph node metastasis, and an advanced Dukes stage. 10 However, the role of MIEN1 in colon cancer progression remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“… 4 , 9 Recently, MIEN1 was reported to be overexpressed in colorectal cancer tissue, and MIEN1 expression level was closely associated with tumor serosal invasion, lymph node metastasis, and an advanced Dukes stage. 10 However, the role of MIEN1 in colon cancer progression remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…By comparing 10 kinds of human mammary carcinoma cell lines and 38 kinds of normal tissue cells, Evans et al reported that C35 was highly expressed in 7 kinds of carcinoma cell lines but barely expressed in normal cells except for Leydig cells (5). Overexpression of C35 was also detected in other cancer cells and tissues such as colorectal cancer and prostate cancer (6,7). The conserved canonical immunoreceptor tyrosinebased activation (ITAM) motif located in its C-terminal end and the last four amino acids CVIL of C35 were proved to have an important role in cancer progression and metastasis (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In China, the incidence of BC has been increasing in recent years, more than 1.6 million patients were diagnosed and 1.2 million death cases occurred each year, among those the newly diagnosed cases accounted for 12.2% (2). C35 is a novel identified tumor biomarker for prediction and early diagnosis of either breast carcinoma (3) or other cancers such as colorectal and prostate cancer (4,5). By comparing 38 kinds of human normal tissue cells including brain cerebellum, endothelium and skeletal muscle, Evans et al revealed that almost all normal cells were negative for C35 expression, with the exception of human leydig cells (6).…”
Section: Introductionmentioning
confidence: 99%